SOME HEAVY METAL LEVELS IN ABDOMINAL MUSCLE OF FRESHWATER CRAYFISH (ASTACUS LEPTODACTYLUS) FROM KEBAN DAM LAKE (ELAZIG, TURKEY) - Canpolat, Ozgur; Dusukcan, Mustafa; Baysal, Nesrin (Parlar Scientific Publications (P S P), 2018)
In this study, it was aimed to investigate bioaccumulation of some heavy metals (Fe, Cu, Cd, Zn, Co, Cr and Pb) in abdominal muscle tissue of Astacus leptodactylus from Agin region of Keban Dam Lake. The levels of Fe, Cu, Cd, Zn, Cd, Co and Cr were found within normal ranges, and lower than the recommended legal limits. The descending order of heavy metal concentrations in the abdominal muscle of crayfish was Fe > Zn > Cu > Co > Cr > Cd. Only Pb was undetected level. The results showed that there was no serious hazard in the abdominal muscle of crayfish from Agin region of Keban Dam Lake (Elazig, Turkey) in terms of the Fe, Cu, Cd, Zn, Cd, Co and Cr values.
Keywords: Crayfish; abdominal muscle tissue; heavy metals; bioaccumulation